UMP boosts aid in TVET - Siti Nur Azwin, Zulkapri (The New Straits Times Press (M) Bhd., 2022)
Universiti Malaysia Pahang (UMP) will continue to strengthen its role as a technology university in the Malaysian Technical University Network (MTUN) to raise the country's Technical and Vocational Training and Education (TVET) empowerment agenda.